MOLECULARLY IMPRINTED POLYMER NANOPARTICLES (MIP-NPs) APPLICATIONS IN ELECTROCHEMICAL SENSORS - FAUZI, DIANE; SAPUTRI, FEBRINA AMELIA (International Journal of Applied Pharmaceutics, 2019)
Molecularly Imprinted Polymers (MIPs) is a polymer that binds together to form a specific binding site that is selective for certain analytes. Its high stability, its synthesize simplicity, and it can ease costs significantly make it was applied widely as a receptor instead of antibodies or enzymes. MIPs can be re-developed into MIPs nanoparticles (MIP-NPs) which have greater potential. MIPs use in electrochemical sensors have relevant applications in daily life and have been tested in human samples. Electrochemical sensors have been successfully functioned with MIP-NPs leading to real-time monitoring of drugs, pesticides, environmental contaminants, and secondary metabolites, as well as molecules with biological relevance. The aim of this review is to summarize the developments and applications of MIP-NPs as a selective recognition component in electrochemical sensors with special emphasis on their analytical applications.